VALUASI EKONOMI PANTAI SAMUDERA INDAH KABUPATEN BENGKAYANG DENGAN METODE TRAVEL COST - , Febrianus Christianto, SSTP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Exploiting of natural resources had in the reality only focused at natural resources yielding service and goods which it is of course have market. While direct which can natural resources consumed by like natural beauty, will become priority both. Indonesia as archipelagic country owning 17.000 island more and have coastline as long as 81.000 km, it is of course have environmental and coastal resource potency of coast representing one of the resource able to consume directly. This research aim to to estimate economic value pantai Samudera Indah. Analyzer the used is analysis of regresi doubled linear and TCM with data cut transversal at pantai Samudera Indah visitors, by using Accidental non Probability Sampling. Independent variable in this research is Travel Cost, Income, Time Went through, Dummy Facility and Dummy Subtitution. Result of from this research indicate that Travel Cost, Time and Dummy Substitution variable have an effect on negativity to Amount of Visit Tourist, Income and Dummy Facility variable have an effect on positive to Amount of Visit Tourist. formed Model can explain 88,09 % influencing the Amount of Visit Tourist and 11,91 % explained by other variable which not be analysed in research model. Known also that Economic Value pantai Samudera Indah by using Travel Cost Method (TCM) that is between Rp13.602.759.743,- dan Rp23.243.791.915,-.